Novel insight into swept frequency eddy-current non-destructive evaluation of material defects. (February 2018) - Janousek, Ladislav; Stubendekova, Andrea; Smetana, Milan
Highlights: New methodology for continuous non-destructive evaluation is proposed. Eddy-current technique is employed for inspection using fixed sensors. Swept-frequency technique helps to unlock potential of eddy-current testing. Frequency response characteristics are investigated in respect to resonance. A value of the resonance frequency depends on crack dimensions. Abstract: Swept frequency eddy-current non-destructive evaluation of defects is concerned in this paper. Possibility of evaluation of detected crack dimensions from response signals is experimentally studied. Two plate specimens having electro-discharge machined slits of various dimensions are inspected using an eddy-current probe. The probe is fixed at a certain position above a specimen during entire inspection of one slit. Frequency of the exciting signal is changed in a wide range in order to acquire frequency response characteristics. The frequency range is adjusted in such a way that the electrical resonance is clearly visible from the acquired characteristics. The characteristics are further processed for exploring their variations in respect to size of inspected slits. Presented results clearly show that the resonance frequency depends on dimensions of a slit. These unique results thus bring new insight into possible utilization of fixed eddy-current sensors driven with swept frequency signal for non-destructive evaluation of cracks.